Enantioselective construction of the ABCDE pentacyclic core of the Strychnos alkaloids - Gammack Yamagata, A; Dixon, D (American Chemical Society, 2017)
An efficient enantioselective 12-step synthesis of the ABCDE pentacyclic core of the Strychnos alkaloids is described. A key feature of this approach is an organocatalyzed enantioselective desymmetrization to generate the morphan core in high ee and dr. After palladium-catalyzed installation of the indole moiety, a subsequent 5-exo-trig dearomatizing atom transfer radical cyclization was developed to construct the C-ring. Following a series of functional group interconversions, the pentacyclic amine core was obtained with all the relevant architecture including five stereocenters pertaining to the Strychnos alkaloids.